2010
DOI: 10.1177/0013124510380716
|View full text |Cite
|
Sign up to set email alerts
|

Truancy Programs: Are the Effects Too Easily Washed Away?

Abstract: Truancy has been identified as a risk factor of criminal behavior but results are mixed as to the best means to reduce this school-based concern. The Truancy Prevention Initiative has been implemented in New Orleans post-Hurricane Katrina under the direction of the Recovery School District to reduce levels of truancy, increase graduation rates, and decrease youth crime. This article emphasizes the statutes and ordinances behind this initiative in order for it to be compared to current evidence-based literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…According to Wilkins and Bost (2016), truancy might indicate that students are potentially disengaged from school and that a trajectory toward dropping out is likely. Truancy has been regarded as a resistance to the school culture (Zhang, 2007) which results in negative developmental outcomes such as deviant behaviors, crime and delinquency (Henry, 2007; Huck, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…According to Wilkins and Bost (2016), truancy might indicate that students are potentially disengaged from school and that a trajectory toward dropping out is likely. Truancy has been regarded as a resistance to the school culture (Zhang, 2007) which results in negative developmental outcomes such as deviant behaviors, crime and delinquency (Henry, 2007; Huck, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…A sharp distinction is constructed between, on the one hand, active human agents who are regarded as using the software as a pedagogical instrument to improve educational practice, and on the other hand, the passive computer software that is being used. This human-centered and individualistic notion of school absence is evident in much of the literature on truancy and school absence (Huck 2011;Kearney and Bensaheb 2006;Reid 2006;Sommer 1985;Veenstra et al 2010). Contrary to this notion, other researchers have shown that school absence is a multifactored problem, emerging in relations between students, families, the culture of the school and the school environment (Claes et al 2009;Corville-Smith et al 1998;Southwell 2006).…”
mentioning
confidence: 98%
“…Nevertheless, individual-centred understandings of students' absences and presences dominate research on school absenteeism. Characteristics related to the individual student's psychological or psychosocial problems, his or her (lack of) abilities or knowledge, and the effects of poorly motivated home environments (Huck 2011;Karlberg & Sundell, 2004;Kearney & Bensaheb 2006;Kozina 2015;Reid 2015;Sommer 1985;Sheppard 2007;Sundell, El-Khouri & Månsson 2005;Veenstra et al 2010) have become recurring explanations for absences.…”
Section: School Absenteeism As An Individual Problemmentioning
confidence: 99%